Field efficacy of a feed-based inactivated vaccine against vibriosis in Cage-Cultured Asian seabass, Lates calcarifer, in Malaysia - Amir-Danial, Zahaludin; Saad, Mohd Zamri; Amal, Mohammad Noor Azmai; Annas, Salleh; Mohamad, Aslah; Jumria, Sutra; Manchanayake, Tilusha; Arbania, Ali; Ina-Salwany, Md Yasin (Multidisciplinary Digital Publishing Institute, 2022)
Vibrio spp. are important aquaculture pathogens that cause vibriosis, affecting large numbers of marine fish species. This study determines the field efficacy of a feed-based inactivated vaccine against vibriosis in cage-cultured Asian seabass. A total of 4800 Asian seabass, kept in a field environment, were separated equally into two groups (vaccinated and non-vaccinated) in duplicate. Fish of Group 1 were orally administered the feed-based vaccine on weeks 0 (prime vaccination), 2 (booster), and 6 (second booster) at 4% body weight, while the non-vaccinated fish of Group 2 were fed with a commercial formulated pellet without the vaccine. Fish gut, mucus, and serum were collected, the length and weight of the fish were noted, while the mortality was recorded at 2-week intervals for a period of 16 weeks. The non-specific lysozyme activities were significantly (p < 0.05) higher in the fish of Group 1 than the non-vaccinated fish of Group 2. Similarly, the specific IgM antibody levels in serum and mucus were significantly (p < 0.05) higher in Group 1 than in Group 2, as seen in the second week, with the highest level 8 weeks after primary immunization. At week 16, the growth performance was significantly (p < 0.05) better in Group 1 and showed lower bacterial isolation in the gut than Group 2. Despite the statistical insignificance (p > 0.05), the survival rate was slightly higher in Group 1 (71.3%) than Group 2 (67.7%). This study revealed that feed-based vaccination improves growth performance, stimulates innate and adaptive immune responses, and increases protection of cultured Asian seabass, L. calcarifer, against vibriosis.